2021
DOI: 10.15586/aei.v49i2.49
|View full text |Cite
|
Sign up to set email alerts
|

Do gender and puberty influence allergic diseases?

Abstract: Differences between biological sex, gender identity, and their impact on health may have significant implications for the prevention, screening, diagnosis, and treatment of several diseases, including allergies. Asthma, allergic rhinitis (AR), atopic dermatitis (AD), and allergic conjunctivitis (AC) have different prevalences and different risk factors in infancy. Although boys present allergies more often in childhood, it quickly changes during girls’ sexual development, leading to lifelong female predominanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 9 publications
2
18
0
2
Order By: Relevance
“…The contribution of important features in minimum panels identi ed in this study to childhood allergic diseases was supported by previous studies. For instance, boys had an increased risk of experiencing allergic disease relative to girls as reported by the majority of studies [28][29][30][31] , consistent with the ndings of the present study, as sex was listed among the top features when predicting the risk for asthma, rhinitis and eczema in children. The reasons for this sex-speci c contribution are not fully understood; however, it might be interpreted by the varying responses to environmental or occupational exposures involving immunological and hormonal factors between boys and girls [32][33][34][35] .…”
Section: Discussionsupporting
confidence: 91%
“…The contribution of important features in minimum panels identi ed in this study to childhood allergic diseases was supported by previous studies. For instance, boys had an increased risk of experiencing allergic disease relative to girls as reported by the majority of studies [28][29][30][31] , consistent with the ndings of the present study, as sex was listed among the top features when predicting the risk for asthma, rhinitis and eczema in children. The reasons for this sex-speci c contribution are not fully understood; however, it might be interpreted by the varying responses to environmental or occupational exposures involving immunological and hormonal factors between boys and girls [32][33][34][35] .…”
Section: Discussionsupporting
confidence: 91%
“…Among boys, allergies are more frequent in childhood; this rapidly changes during girls’ sexual development, with a lifelong predominance of allergic diseases in females. Such a finding might be ascribed to the influence of sex hormones, differences in lifestyles, diet, and adherence to treatment, but it deserves to be further investigated [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that the relative amounts of lipids were also linked to the sex of the dogs; some lipids, specifically sphingolipids, CEs, and PLs, were affected differently by AD in males and in females. In human patients, epidemiological studies have shown that AD is more prevalent in females after puberty but can be more severe in males, suggesting a role of sex hormones [ 2 , 35 , 36 , 37 ]. On the other hand, there appears to be no sexual predisposition in dogs to the development of AD [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%